2022
DOI: 10.3390/pr10071235
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbents Used for Microcystin Removal from Water Sources: Current Knowledge and Future Prospects

Abstract: The increasing occurrence of toxic cyanobacteria in water sources, driven by climate change and eutrophication, is of great concern worldwide today. Cyanobacterial blooms can negatively affect water bodies and generate harmful secondary metabolites, namely microcystins (MCs), which significantly impair water quality. Various adsorbents used for MC removal from water sources were assessed in this investigation. Activated carbon constitutes the most widely used adsorbent for treating contaminated waters due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 159 publications
0
7
0
Order By: Relevance
“…This consequently facilitates charge attraction or repulsion between the toxin and adsorbent. The MCLR molecule contains carboxylic acid groups and amino acid groups, imparting a negative charge at pH values 3 and 12 69 . This explains the higher removal efficiency at lower pH, as electrostatic attraction aids adsorption, while at higher pH, repulsion ensues between the toxins and biochar, limiting uptake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This consequently facilitates charge attraction or repulsion between the toxin and adsorbent. The MCLR molecule contains carboxylic acid groups and amino acid groups, imparting a negative charge at pH values 3 and 12 69 . This explains the higher removal efficiency at lower pH, as electrostatic attraction aids adsorption, while at higher pH, repulsion ensues between the toxins and biochar, limiting uptake.…”
Section: Resultsmentioning
confidence: 99%
“…As for the hydrogen bonding, the biochar contains substantial amount of acidic oxygen containing function groups of 941.33 ± 0.86 µmol/g (Table S1 ) which are favorable for chemisorption. These chemical interactions may arise via the polar or polarizable MCLR molecules and the oxygen containing functional groups present on the biochar 69 , 82 . Hydrophobic interactions play interesting roles for the uptake of MCLR onto biochar.…”
Section: Resultsmentioning
confidence: 99%
“…All of this has a direct impact on the electrostatic interactions. According to El Bouaidi et al [28], the adsorption of MC-LR has been demonstrated to increase with a decrease in pH (from 8 to 2.5). Under acidic conditions, the weak acidic functional groups of MCs are presumed to become available for adsorption [28], and this probably explains the significantly higher adsorption of the Diaion ® HP-20 at site H2, which had waters with slightly neutral pH values.…”
Section: Levels Of Mcs Detected By the Spatt Samplersmentioning
confidence: 99%
“…According to El Bouaidi et al [28], the adsorption of MC-LR has been demonstrated to increase with a decrease in pH (from 8 to 2.5). Under acidic conditions, the weak acidic functional groups of MCs are presumed to become available for adsorption [28], and this probably explains the significantly higher adsorption of the Diaion ® HP-20 at site H2, which had waters with slightly neutral pH values. With regards to the chitosan-based substrates, the amino groups in the chitosan polymer are known to protonate as -NH 3+ in neutral conditions, and the MC-LR has two carboxylate (-COO − ) groups under such conditions for electrostatic interactions to take place.…”
Section: Levels Of Mcs Detected By the Spatt Samplersmentioning
confidence: 99%
See 1 more Smart Citation